Ivabradine-Stimulated Microvesicle Release Induces Cardiac Protection against Acute Myocardial Infarction - Ramirez-Carracedo, Rafael (Int J Mol Sci, 2020)
Ivabradine can reduce heart rate through inhibition of the current I(f) by still unexplored mechanisms. In a porcine model of ischemia reperfusion (IR), we found that treatment with 0.3 mg/kg Ivabradine increased plasma release of microvesicles (MVs) over Placebo, as detected by flow cytometry of plasma isolated from pigs 7 days after IR, in which a tenfold increase of Extracellular Matrix Metalloproteinase Inducer (EMMPRIN) containing (both high and low-glycosylated) MVs, was detected in response to Ivabradine. The source of MVs was investigated, finding a 37% decrease of CD31+ endothelial cell derived MVs, while CD41+ platelet MVs remained unchanged. By contrast, Ivabradine induced the release of HCN4+ (mostly cardiac) MVs. While no differences respect to EMMPRIN as a cargo component were found in endothelial and platelet derived MVs, Ivabradine induced a significant release of EMMPRIN+/HCN4+ MVs by day 7 after IR. To test the role of EMMPRIN+ cardiac MVs (EMCMV), H9c2 cell monolayers were incubated for 24 h with 10(7) EMCMVs, reducing apoptosis, and increasing 2 times cell proliferation and 1.5 times cell migration. The in vivo contribution of Ivabradine-induced plasma MVs was also tested, in which 10(8) MVs isolated from the plasma of pigs treated with Ivabradine or Placebo 7 days after IR, were injected in pigs under IR, finding a significant cardiac protection by increasing left ventricle ejection fraction and a significant reduction of the necrotic area. In conclusion ivabradine induces cardiac protection by increasing at least the release of EMMPRIN containing cardiac microvesicles.